A mesoscale approach for modeling capillary water absorption and transport phenomena in cementitious materials. (15th April 2018) - Caggiano, Antonio; Said Schicchi, Diego; Mankel, Christoph; Ukrainczyk, Neven; Koenders, Eduardus A.B.
Highlights: A mesoscale FE model is proposed for simulating moisture movements. Moisture evolution in partly-saturated porous media is driven by capillary forces. ITZs around aggregates are explicitly modeled as porous elements. Microstructure and ITZ morphology determine moisture evolution. Permeability models are based on an explicit description of capillary pores. Abstract: This paper proposes a mesoscale approach for simulating moisture transport by capillary action in partly-saturated porous cementitious composites. The modeling approach explicitly accounts for moisture transport through a mesostructure composed of coarse aggregates, surrounding cementitious mortar and interfaces. These latter, namely interface transition zones (ITZs), allow to describe the interaction between aggregates and mortar, and may cause an alternative path for the internal moisture movements. Basic morphology effects of the ITZs are simulated using a ribbon approach. Random spatial distribution of cement particles are stacked in the meso-geometry. Aggregate particles are introduced as randomly perturbed polygons and the moisture transport is modeled as a diffusion problem and solved by means of the finite element method. The proposed constitutive models are based on a proper description of the permeability and pore size distribution which strongly affect the local moisture content. Numerical results at both macro- and mesoscale levels demonstrate the soundness and capability of the proposed approach. The integrated modeling results actually demonstrate the potential of the mesoscale approach and shows the role of the ITZs as an internal interconnected network.